Dynamic simulation and control system for chemical looping combustion - Thanapat Wanotayaroj; Benjapon Chalermsinsuwan; Pornpote Piumsomboon (Energy Reports, 2020)
Chemical looping combustion (CLC) is a technique for separating carbon dioxide from flue gas. It consists of two main processes: a fuel reactor and an air reactor. In the fuel reactor, fuel reacts with solid metal oxide particles to produce heat, CO2 and H2O vapor which later can be easily separated by the condensation. The reacted solid metal is then sent to the air reactor for regenerating via an oxidation reaction with air before being returned to the fuel reactor. In this study, these reactors in the CLC system are integrated as a circulating fluidized bed system and a dynamic model has been developed for the system. The fuel reactor (or downer) operates in bubbling fluidization regime where the air reactor (or riser) operates in fast fluidization regime. Using the developed dynamic model, the transient responses of various control variables such as the temperature of two fluidized bed reactors, pressure and the liquid level of a condenser have been controlled by manipulating variables such as heat transfer rates of the reactors, gas outlet flow rate and liquid outlet flow rate of the condenser. A proportional-integral-derivative (PID) controller was tuned for controlling purpose. The integral of the absolute value of error (IAE) is used to evaluate the control system performance.
Keywords: 330; Aspen Dynamics; Chemical looping combustion; Dynamic simulation; Fluidized bed reactors